WATER TRANSPORT LIKE THE CONDITIONAL FACTOR AND TO WAYS FOR DEVELOPMENT OF TURIZM OF MEDZIBODROZIE (Perner's Contacts, 2009)
The locality of the Medzibodrog region creates suppositions for turist development, especially in waterway turism. This regoin is specified by unique nature and also culture. My thesis analyses actual fairway conditions, especially on river Bodrog.
Keywords: river Bodrog; Medzibodrožie; tourist traffic; touring by water